ROLE OF EFFECTIVE COMMUNICATION IN ENHANCING DOG OWNER KNOWLEDGE ABOUT BREEDING PRACTICES IN PUNJAB - ROOPA, Y; KASRIJA, R; VERMA, H K; SINGH, P (The Indian Journal of Animal Reproduction, 2022)
At Teaching Veterinary University Hospital and various districts of Punjab, the dog owners (100 each fromurban and rural area) were randomly selected and personally interviewed using pretested interview schedule.Breeding knowledge score of both groups was different (p
Keywords: Breeding practice; Communication; Dog; Knowledge; Punjab